Solar Tracker Platform Development for Energy Efficiency Improvement of Photovoltaic Panels - Szász, Csaba (Recent Innovations in Mechatronics, 2019)
Solar energy systems have emerged over the last decades as the cleanest and most abundant renewable energy resources available worldwide. Solar trackers are devices specially developed to enhance the energy efficiency of solar energy systems. This paper presents the design and implementation stages of a reconfigurable hardware technology-based two-axis solar tracker platform, specially conceived to improve the energy efficiency of photovoltaic (PV) panels. The main module of this platform is the NI-MyRIO ready-to-use development system built upon a high-performance Field Programmable Gate Array (FPGA) processor that controls the entire solar tracker unit. Optimal tracking of the sun movement and obtaining the maximal energy efficiency rate is achieved by simultaneous real-time controlling both the captured sunlight intensity and PV cell temperature magnitudes. In this way, a robust and versatile positioning system has been developed that performs a high precision and accurate tracking pathway. All the control algorithms are implemented there under the LabView graphical programming software toolkit. The final solution boosts in a useful and modularized tracking system that looks useful in a wide range of applications both in industrial and domestic project sites with different power scales.